Spatially rearranged object parts can facilitate perception of intact whole objects - Cacciamani, Laura; Ayars, Alisabeth A.; Peterson, Mary A. (Frontiers in Psychology, 2014)
The familiarity of an object depends on the spatial arrangement of its parts; when the parts are spatially rearranged, they form a novel, unrecognizable configuration. Yet the same collection of parts comprises both the familiar and novel configuration. Is it possible that the collection of familiar parts activates a representation of the intact familiar configuration even when they are spatially rearranged? We presented novel configurations as primes before test displays that assayed effects on figure-ground perception from memories of intact familiar objects. In our test displays, two equal-area regions shared a central border; one region depicted a portion of a familiar object. Previous research with such displays has shown that participants are more likely to perceive the region depicting a familiar object as the figure and the abutting region as its ground when the familiar object is depicted in its upright orientation rather than upside down. The novel primes comprised either the same or a different collection of parts as the familiar object in the test display (part-rearranged and control primes, respectively). We found that participants were more likely to perceive the familiar region as figure in upright vs. inverted displays following part-rearranged primes but not control primes. Thus, priming with a novel configuration comprising the same familiar parts as the upcoming figure-ground display facilitated orientation-dependent effects of object memories on figure assignment. Similar results were obtained when the spatially rearranged collection of parts was suggested on the groundside of the prime’s border, suggesting that familiar parts in novel configurations access the representation of their corresponding intact whole object before figure assignment. These data demonstrate that familiar parts access memories of familiar objects even when they are arranged in a novel configuration.